The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.29333/ejmste/13458
|View full text |Cite
|
Sign up to set email alerts
|

The interactive classroom: Integration of SMART notebook software in chemistry education

Abstract: The integration of SMART notebook software was one of the modifications to the teaching and learning environment since the post-coronavirus. Despite the extent of literature about the importance of this software to teaching and learning, there have been conflicting views and an overall lack of intervention in the Gambia regarding its importance in chemistry teaching and learning. Nevertheless, studies conducted about the impact of this software in the Gambia traditionally focused on evaluating regional examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…An interactive classroom enhances this skill through the participation of students in active learning. It shows that technology integration supports their problem-solving capabilities through practice (Jammeh et al, 2023). Besides that, particularly in laboratory circumstances, this supports problem-solving during hands-on activities as highlighted by Zemel et al,(2021).…”
Section: C) Problem-solvingmentioning
confidence: 67%
See 4 more Smart Citations
“…An interactive classroom enhances this skill through the participation of students in active learning. It shows that technology integration supports their problem-solving capabilities through practice (Jammeh et al, 2023). Besides that, particularly in laboratory circumstances, this supports problem-solving during hands-on activities as highlighted by Zemel et al,(2021).…”
Section: C) Problem-solvingmentioning
confidence: 67%
“…Implementing tools like digital badges improved students' conceptual understanding by comparing the number of badges to represent students' conceptual understanding (Boesdorfer & Daugherty, 2020). In contrast, Jammeh et al (2023) found that using SMART notebook software that contains interactive worksheets with a fast response system significantly improved conceptual and academic achievements. Assessment tools with technology foster an in-depth understanding of the Lewis acid-base model.…”
Section: Research Question 2: How Does the Implementation Of Varied F...mentioning
confidence: 83%
See 3 more Smart Citations